Factors of Shaping the Image of the Professions of the Future among High School Students - Irina Kulikovskaya; Evgeniya Mironova (ARPHA Proceedings, 2022)
The paper reveals the concept of “the image of the professions of the future” and the relevance of its formation in modern life conditions. The factors influencing the formation of images of the future, as well as methods of studying the image of the professions of the future among high school students, have been determined. The image of the professions of the future, being one of the most important components of a holistic picture of the world, is a set of ideas about the profession, its value in society and about oneself as a possible representative of the professional community with the necessary competencies. The study of the process of shaping the image of the professions of the future in adolescents contributes to scientific ideas about the development of their worldview. The research in this area, which actualizes modern trends in the study of the characteristics of the younger generation, is presented. One of the important areas of interest for high school students is to study and plan options for their future profession. Scientists consider the image of the professions of the future as a connection between the current life situation of a student and the promising life aspirations of a high school student, which determine the possibility of their implementation in the future. According to the principles of career guidance, high school students are at the stage of studying professional growth, which includes crystallizing and clarifying their professional preferences, as well as making preliminary decisions about choosing a profession.